Polar plate as well as preparation method and application thereof
By setting thickness variation sections and electrode slurry coating on the titanium mesh of the electrode plate, the problem of uneven distribution of electrons of the electrochemical deintercalation plate is solved, and a more uniform potential distribution and more efficient lithium extraction performance are achieved, while reducing material costs.
Patent Information
- Application Number
- CN202411738914.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
AI Technical Summary
The existing electrochemical deintercalation plates have uneven electron distribution on the electrode surface at different positions from the current input and output terminals, which affects the electrochemical lithium extraction performance.
A electrode plate is designed, which includes a titanium mesh and an electrode paste coating on at least one side of the titanium mesh. The titanium mesh has a thickness change segment along the direction of the current input end to the output end to ensure that the thicknesses of each position are equal.
Through the design of the thickness change section, the pressure drop of the titanium mesh itself is reduced, the uniformity of the electrode plate potential distribution is improved, and the full performance of lithium-enhancing performance is ensured, while the strength of the titanium mesh is increased without significantly increasing the material cost.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polar plates, and in particular to a polar plate and a preparation method and application thereof. Background Art
[0002] As an important element for automobile electrification, the demand for lithium is increasing day by day. As one of the important sources of lithium resources, salt lake brine has attracted much attention. In order to extract lithium from salt lake brine, various methods have emerged. Electrochemical deintercalation and lithium extraction technology has become one of the mainstream directions due to its high selectivity, low energy consumption, and environmental protection. By selecting materials with high selectivity for deintercalation of lithium as electrode materials (such as lithium iron phosphate and lithium manganese oxide, etc.), the reversible deintercalation of lithium is completed under the action of an electric field, thereby achieving efficient extraction of lithium resources.
[0003] However, the plates currently used for electrochemical deintercalation usually have the problem of uneven distribution of electrons on the electrode surface at different positions away from the current input and output ends, which affects the performance of electrochemical lithium extraction.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The object of the present invention is to provide a polar plate and a preparation method and application thereof, so as to solve or improve the above technical problems.
[0006] The present invention can be implemented like this:
[0007] In a first aspect, the present invention provides an electrode plate, which includes a titanium mesh and an electrode slurry coating disposed on at least one side of the titanium mesh;
[0008] The electrode plate has a first end and a second end that are arranged opposite to each other, either of which is a current input end and the other is a current output end; along the direction from the first end to the second end, the thickness of each position of the electrode plate is equal and the titanium mesh has a thickness variation section.
[0009] In an optional embodiment, the thickness of the thickness-varying section gradually increases or decreases along the direction from the first end to the second end.
[0010] In an optional embodiment, the thickness of the titanium mesh is 0.7 mm to 3 mm, and the thickness of the electrode slurry coating disposed on the surface of any one side of the titanium mesh is ≥ 2 mm.
[0011] In an optional embodiment, the surface of the titanium mesh on which the electrode slurry coating is disposed is rectangular, and the ratio of the length of the long side to the short side of the rectangle is 1.5:1 to 2:1.
[0012] In an optional embodiment, the electrode plate further includes a pole ear, and the pole ear is arranged on the long side of the rectangle.
[0013] In an optional embodiment, the thickness of the thickness variation section gradually increases from close to the pole lug to away from the pole lug.
[0014] In an optional embodiment, 0≤the distance between the electrode tab and a short side of the rectangle≤1 / 3 of the length of the long side of the rectangle.
[0015] In a second aspect, the present invention provides a method for preparing a polar plate as described in any one of the aforementioned embodiments, comprising the following steps: coating electrode slurry on at least one side of a titanium mesh, and drying.
[0016] In an optional embodiment, the material used to make the titanium mesh includes at least one of pure titanium and titanium alloy.
[0017] In an optional embodiment, the titanium alloy includes at least one of a titanium-copper alloy, a titanium-nickel alloy, a titanium-palladium alloy, and a titanium-molybdenum alloy.
[0018] In an optional embodiment, the raw materials for preparing the electrode slurry include a delithiation active material, a conductive agent, a binder and a solvent;
[0019] Among them, the mass ratio of the delithiation active material, the conductive agent and the binder is (80-85):(6-10):(5-11).
[0020] In an optional embodiment, the delithiation active material is obtained by partially reducing the active material with an oxidizing solution, and the active material includes one of lithium iron phosphate, lithium-rich manganese-based, lithium iron manganese phosphate and lithium manganate materials.
[0021] In an alternative embodiment, the delithiation amount of the delithiation active material is 20% to 60%.
[0022] In an optional embodiment, the oxidizing solution includes one of a sodium persulfate solution, a hydrogen peroxide solution, and a potassium permanganate solution.
[0023] In an alternative embodiment, the concentration of the oxidizing solution is 0.25 wt % to 0.5 wt %.
[0024] In an optional embodiment, the preparation raw material further includes a pore former.
[0025] In an alternative embodiment, the pore former comprises a soluble salt.
[0026] In an alternative embodiment, the pore former includes at least one of sodium chloride, lithium chloride and magnesium chloride.
[0027] In an alternative embodiment, the mass of the pore former is 5% to 40% of the active material.
[0028] In a third aspect, the present invention provides a use of a plate according to any one of the aforementioned embodiments in electrochemical lithium extraction.
[0029] In an optional embodiment, the plate is used for electrochemical lithium extraction from salt lakes.
[0030] The beneficial effects of the present invention include:
[0031] The present invention can change the thickness of the titanium mesh at different positions by setting a thickness variation section on the titanium mesh. On the one hand, it can effectively reduce the voltage drop generated by the titanium mesh itself, improve the uniformity of the plate potential distribution, and ensure the full play of the plate lithium extraction performance; on the other hand, it can effectively improve the strength of the titanium mesh without significantly increasing the material cost. The plate can be used for electrochemical lithium extraction, especially electrochemical salt lake lithium extraction, and has a good lithium extraction effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0033] Figure 1 Schematic diagram of the structure of the electrode plates prepared in Examples 1 to 4 and Comparative Examples 1 to 2 of the present invention at a first viewing angle, wherein the cross-sectional direction is from the side away from the electrode ear to the side close to the electrode ear and is perpendicular to the direction of the electrode ear 10;
[0034] Figure 2 The electrode edge prepared in Example 1 and Example 2 of the present invention Figure 1 The cross-sectional view obtained from the section direction;
[0035] Figure 3 The electrode edge prepared in Example 3 of the present invention Figure 1 The cross-sectional view obtained from the section direction;
[0036] Figure 4 The electrode edge prepared in Example 4 of the present invention Figure 1 The cross-sectional view obtained from the section direction;
[0037] Figure 5 The electrode edge prepared in Example 5 of the present invention Figure 1 The cross-sectional view obtained from the section direction;
[0038] Figure 6 The electrode edge prepared in Example 6 of the present invention Figure 1 The cross-sectional view obtained from the section direction;
[0039] Figure 7 The electrode edges prepared in Comparative Examples 1 and 2 of the present invention are Figure 1The cross-sectional view obtained from the section direction;
[0040] Figure 8 Schematic diagram of resistance test of titanium mesh and electrode plate in Examples 1 to 6 and Comparative Examples 1 to 2.
[0041] Icon: 10-ear; 20-electrode slurry coating; 30-titanium mesh; 31-upper surface; 32-lower surface; 40-resistance meter. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0043] The electrode plate provided by the present invention and its preparation method and application are described in detail below.
[0044] Please combine Figures 1 to 6 The present invention provides an electrode plate, which includes a titanium mesh 30 and an electrode slurry coating 20 disposed on at least one side of the titanium mesh 30;
[0045] The electrode plate has a first end and a second end that are arranged opposite to each other, either of which is a current input end and the other is a current output end; along the direction from the first end to the second end, the thickness of each position of the electrode plate is equal and the titanium mesh 30 has a thickness variation section.
[0046] In the present invention, the thickness of a certain position of the electrode plate is the sum of the thickness of the titanium mesh 30 and the thickness of the electrode slurry coating 20 at that position.
[0047] In some optional embodiments, the electrode slurry coating 20 (eg, Figure 5 and Figure 6 ); In other optional embodiments, the electrode slurry coating 20 (such as Figures 1 to 4 The titanium mesh 30 has an upper surface 31 and a lower surface 32 that are arranged opposite to each other. The electrode slurry coating 20 may be arranged on the upper surface 31 or the lower surface 32, or may be arranged on both the upper surface 31 and the lower surface 32. Accordingly, the thickness variation section of the titanium mesh 30 corresponds to the position where the electrode slurry coating 20 is arranged.
[0048] In some optional embodiments, the thickness of the titanium mesh 30 varies from the first end to the second end (eg Figure 2In other embodiments, the thickness of part of the titanium mesh 30 changes from the first end to the second end, and the thickness of the remaining part remains the same. That is, in this manner, the titanium mesh 30 has a thickness variation section and a thickness equal section (such as Figure 3 and Figure 4 ).
[0049] In the above-mentioned methods, the change form of the titanium mesh 30 is not limited, for example, it can change uniformly (such as uniformly and gradually decreasing, or uniformly and gradually increasing), or it can change non-uniformly (such as first decreasing and then increasing, or first increasing and then decreasing), or it can also change in a step-by-step manner.
[0050] In some typical embodiments, the thickness of the thickness variation section increases or decreases uniformly along the direction from the first end to the second end. In some more typical embodiments, the upper surface 31 and the lower surface 32 of the titanium mesh 30 are both provided with an electrode slurry coating 20, and the thickness of the titanium mesh 30 changes along the direction from the first end to the second end, and the thickness of the titanium mesh 30 increases or decreases uniformly. In this typical manner, the voltage drop generated by the titanium mesh 30 itself can be effectively reduced, the uniformity of the plate potential distribution can be improved, and the polarization of the plate can be reduced, which is conducive to the performance of lithium extraction.
[0051] In some optional embodiments, the thickness of the titanium mesh 30 may be 0.7 mm to 3 mm, such as 0.7 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm or 3 mm, or may be other values within the range of 0.7 mm to 3 mm.
[0052] The thickness of the electrode slurry coating 20 disposed on any side of the titanium mesh 30 is ≥ 2 mm, such as 2 mm, 2.5 mm, 3 mm, 5 mm, 8 mm or 10 mm, etc., which is set according to actual needs. If the thickness of the electrode slurry coating 20 disposed on any side of the titanium mesh 30 is less than 2 mm, the loading amount of active material on a single titanium mesh is reduced, which is not conducive to the improvement of lithium extraction performance.
[0053] In some optional embodiments, the surface of the titanium mesh 30 on which the electrode slurry coating 20 is disposed is rectangular, and the length ratio of the long side to the short side of the rectangle can be 1.5:1 to 2:1, such as 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2:1, etc., or other values within the range of 1.5:1 to 2:1. If the length ratio of the long side to the short side is less than 1.5:1 (such as 1.2:1), the longest distance between the pole ear and the plate surface is elongated, which is not conducive to the electric field distribution on the plate surface; if the length ratio of the long side to the short side is greater than 2:1 (such as 2.5:1), it is not conducive to the uniform distribution of the electric potential at various locations on the plate surface, thereby reducing the lithium extraction performance.
[0054] In some optional embodiments, the upper surface 31 and the lower surface 32 of the electrode plate are rectangular, and the side surfaces are trapezoidal.
[0055] In the present invention, the titanium mesh 30 can be formed by stamping a titanium plate or weaving a titanium wire. The mesh structure can exemplarily but not limitatively include at least one of a diamond, trapezoidal, square and circular structure. The preparation material of the titanium mesh 30 can exemplarily include at least one of pure titanium and a titanium alloy, wherein the titanium alloy can exemplarily but not limitatively include at least one of a titanium-copper alloy, a titanium-nickel alloy, a titanium-palladium alloy and a titanium-molybdenum alloy.
[0056] For example, the processing technology of the special structure titanium mesh 30 can be at least one of stretching, rolling, powder metallurgy, machining, lamination welding, electroplating, vapor deposition and 3D printing. The machined titanium mesh 30 can be cut into corresponding sizes by at least one of shearing, laser cutting, water jet cutting and wire cutting.
[0057] In the present invention, the electrode plate may further include an electrode tab 10 , and the electrode tab 10 is disposed on the long side of the rectangle.
[0058] In some typical embodiments, the thickness of the thickness variation section of the titanium mesh 30 gradually increases from close to the pole lug 10 to away from the pole lug 10 . The increasing direction may be perpendicular to the direction of the pole lug 10 .
[0059] In some optional embodiments, 0≤the distance between the tab 10 and a short side of the rectangle≤1 / 3 of the length of the long side of the rectangle. Controlling the location of the tab 10 within the above range can help shorten the distance difference between the tab and various locations on the plate surface, thereby reducing the potential difference.
[0060] As mentioned above, by changing the thickness of the titanium mesh 30 at different positions, on the one hand, the voltage drop generated by the titanium mesh 30 itself can be effectively reduced, the uniformity of the plate potential distribution can be improved, and the full play of the lithium extraction performance of the plate can be ensured; on the other hand, the strength of the titanium mesh 30 can be effectively improved without significantly increasing the material cost.
[0061] The above-mentioned plate with a thickness variation section improves the problem of large intrinsic resistance of the titanium mesh 30 and uneven potential distribution on the electrode surface. Among them, the thickness of the titanium mesh 30 gradually increases from the short side of the side closer to the pole ear 10 to the short side of the other side farther from the pole ear 10 (the thickness increasing direction is perpendicular to the direction of the pole ear 10); by setting the electrode slurry coating 20 on the surface of the titanium mesh 30, the overall thickness of the plate is uniform, and the corresponding internal electron distribution of the plate is more uniform. According to R=ρL / S (where R is the resistance of the titanium mesh 30, ρ is the density of the titanium mesh 30, L is the distance from a certain position in the titanium mesh 30 to the pole ear 10, and S is the cross-sectional area of the titanium mesh 30), it can be seen that the thicker the titanium mesh 30, the larger S is, and the smaller the resistance is. By increasing the thickness of the titanium mesh 30 at the far pole ear 10, the voltage difference of the titanium mesh 30 on both sides far from the pole ear 10 and near the pole ear 10 is increased, thereby shortening the voltage drop at both ends of the plate, which is conducive to the improvement of the lithium extraction performance of the lithium extraction electrode.
[0062] Correspondingly, the present invention also provides a method for preparing the above-mentioned electrode plate, comprising the following steps: coating the electrode slurry on at least one side of the titanium mesh 30, and drying.
[0063] Specifically, the electrode slurry is coated according to the titanium mesh 30 used for the electrode plate, so that the thickness of the titanium mesh 30 at each location is equal to the sum of the slurry coating thickness.
[0064] In some optional embodiments, the raw materials for preparing the electrode slurry may include a delithiation active material, a conductive agent, a binder, and a solvent.
[0065] Among them, the mass ratio of the delithiation active material, the conductive agent and the binder can be (80-85):(6-10):(5-11), such as 80:10:10, 84:6:10, 85:8:7, 83:6:11, 85:10:5 or 82:8:10, or other values within the range of (80-85):(6-10):(5-11).
[0066] In some optional embodiments, the delithiation active material is obtained by partially reducing the active material with an oxidizing solution, wherein the active material may illustratively but not limitatively include one of lithium iron phosphate, lithium-rich manganese-based, lithium manganese iron phosphate and lithium manganate materials.
[0067] The delithiation amount of the above-mentioned delithiation active material can be 20% to 60%, such as 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or 60%, etc., or other values within the range of 20% to 60%. If the delithiation amount of the delithiation active material is too high (such as 80%), the actual delithiation vacancy is only 100%, which will result in a loss of 60% of the lithium source, and the economic cost is relatively low.
[0068] In some optional embodiments, the oxidizing solution may illustratively but not limitatively include one of a sodium persulfate solution, a hydrogen peroxide solution, and a potassium permanganate solution.
[0069] The concentration of the oxidizing solution may be 0.25 wt% to 0.5 wt%, such as 0.25 wt%, 0.3 wt%, 0.35 wt%, 0.4 wt%, 0.45 wt% or 0.5 wt%, etc., or may be other values within the range of 0.25 wt% to 0.5 wt%.
[0070] In specific operation, the active material can be immersed in an oxidizing solution to obtain the delithiation active material, wherein the immersion time can be exemplarily 2 hours.
[0071] In some optional embodiments, the conductive agent may illustratively but not limitatively include at least one of conductive carbon black (SP), carbon nanotubes (CNT), graphene (GN), and carbon fiber (CF).
[0072] In some optional embodiments, the binder may illustratively but not limitatively include at least one of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA) and styrene-butadiene rubber (SBR).
[0073] In some optional embodiments, the solvent may illustratively but not limitatively include at least one of N-methylpyrrolidone, dimethylformamide, acetone and dimethyl sulfoxide. The mass of the solvent may be 110% to 130% of the total mass of the active material, the binder and the conductive agent.
[0074] In some optional embodiments, the preparation raw material may further include a pore former.
[0075] The pore former includes a soluble salt, and may illustratively but not limitedly include at least one of sodium chloride, lithium chloride, and magnesium chloride.
[0076] The mass of the pore former may be 5% to 40% of the active material, such as 5%, 10%, 15%, 20%, 25%, 30%, 35% or 40%, etc., or other values within the range of 5% to 40%.
[0077] In addition, the present invention also provides an application of the above-mentioned electrode plate in electrochemical lithium extraction. For example, the above-mentioned electrode plate can be used for electrochemical lithium extraction from salt lakes.
[0078] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0079] Example 1
[0080] This embodiment provides a plate (such as Figure 1 The preparation method thereof comprises the following steps:
[0081] S1: preparing a titanium mesh 30 with a tab 10 .
[0082] A titanium plate made of pure titanium with a thickness of 2 mm was used to obtain a titanium mesh 30 with a special structure having a thickness gradient distribution through mechanical processing. Subsequently, a titanium mesh 30 with diamond-shaped mesh holes was obtained through punching processing, and it was cut into a titanium mesh 30 with a width of 19 cm and a length of 33 cm. The upper surface 31 and the lower surface 32 of the titanium mesh 30 are rectangular, and the side surface is an isosceles trapezoid. The thickness of the thinnest part of the titanium mesh 30 is 1 mm, and the thickness of the thickest part is 2 mm. The cross-sectional schematic diagram of the titanium mesh 30 is shown in FIG. Figure 2 A titanium plate with a length of 5 cm and a width of 5 cm is used as the pole lug 10, and the pole lug 10 is welded to one long side of the titanium mesh 30 and close to the end of the titanium mesh 30 with a thinner thickness (the short side corresponding to the end of the titanium mesh 30 with a thinner thickness is defined as the first short side), and the distance between the center of the pole lug 10 and the first short side is 5 cm.
[0083] S2: preparing electrode slurry.
[0084] Under stirring, the binder PVDF, the lithium iron phosphate powder after delithiation (the amount of lithium desorption is 20wt%), and the conductive agent (by mass ratio, SP:CNT=5:3) are added to the solvent NMP in the mass ratio of 8:82:10, and finally the pore-forming agent NaCl is added, and the amount added is 35% of the active material. Among them, the lithium iron phosphate powder after delithiation is obtained by immersing the lithium iron phosphate powder in a sodium persulfate solution with a concentration of 0.4wt% for 2h.
[0085] S3: Prepare the electrode plates.
[0086] The titanium mesh 30 with the pole ear 10 obtained in S1 is fixed on the coating mold, and then the electrode slurry obtained in S2 is coated on the upper surface 31 and the lower surface 32 of the titanium mesh 30 to ensure that the surface of the electrode slurry coating 20 is flush with the surface of the coating mold. The thickness of the coating at the thinnest point is about 2 mm, and the coating area is 17 cm×31 cm. After the coating is completed, it is dried to obtain the electrode plate.
[0087] The total thickness of the plate is equal at all locations.
[0088] Example 2
[0089] This embodiment provides a plate (such as Figure 1 The preparation method thereof comprises the following steps:
[0090] S1: preparing a titanium mesh 30 with a tab 10 .
[0091] The only difference between this step and S1 in Example 1 is that the thickness of the thinnest part of the titanium mesh 30 is 0.7 mm.
[0092] S2: preparing electrode slurry.
[0093] This step is the same as S2 in Example 1.
[0094] S3: Prepare the electrode plates.
[0095] This step is the same as S2 in Example 1.
[0096] The total thickness of the plate is equal at all locations.
[0097] Example 3
[0098] This embodiment provides a plate (such as Figure 1 The preparation method thereof comprises the following steps:
[0099] S1: preparing a titanium mesh 30 with a tab 10 .
[0100] A titanium plate made of pure titanium with a thickness of 2 mm was used, and a special structure titanium mesh 30 was obtained by mechanical processing, which was composed of a thickness gradient distribution and a uniform thickness of 0.7 mm. Subsequently, a titanium mesh 30 with diamond mesh holes was obtained by punching, and it was cut into a titanium mesh 30 with a width of 19 cm and a length of 33 cm. The upper surface 31 and the lower surface 32 of the titanium mesh 30 in the thickness gradient distribution area are rectangular, and the side surface is an isosceles trapezoid. The thickness of the thinnest part of the titanium mesh 30 is 0.7 mm, and the thickness of the thickest part is 2 mm. The cross-sectional schematic diagram of the titanium mesh 30 is shown in FIG. Figure 3 A titanium plate with a length of 5 cm and a width of 5 cm is used as the pole lug 10, and the pole lug 10 is welded to one long side of the titanium mesh 30 and close to the end of the titanium mesh 30 with a thinner thickness (the short side corresponding to the end of the titanium mesh 30 with a thinner thickness is defined as the first short side), and the distance between the center of the pole lug 10 and the first short side is 5 cm.
[0101] S2: preparing electrode slurry.
[0102] This step is the same as S2 in Example 1.
[0103] S3: Prepare the electrode plates.
[0104] This step is the same as S2 in Example 1.
[0105] The total thickness of the plate is equal at all locations.
[0106] Example 4
[0107] This embodiment provides a plate (such as Figure 1 The preparation method thereof comprises the following steps:
[0108] S1: preparing a titanium mesh 30 with a tab 10 .
[0109] A titanium plate made of pure titanium with a thickness of 2 mm was used, and a titanium mesh 30 with a special structure consisting of a thickness gradient distribution and a uniform thickness of 0.7 mm was obtained by mechanical processing. Subsequently, a titanium mesh 30 with diamond mesh holes was obtained by punching, and it was cut into a titanium mesh 30 with a width of 19 cm and a length of 33 cm. The upper surface 31 and the lower surface 32 of the titanium mesh 30 in the thickness gradient distribution area are rectangular, and the side surface is an isosceles trapezoid. The thickness of the thinnest part of the titanium mesh 30 is 0.7 mm, and the thickness of the thickest part is 2 mm. The cross-sectional schematic diagram of the titanium mesh 30 is shown in FIG. Figure 4 A titanium plate with a length of 5 cm and a width of 5 cm is used as the pole lug 10, and the pole lug 10 is welded to one side of the long side of the titanium mesh 30 and close to the thicker end of the titanium mesh 30 (the short side corresponding to the thicker end of the titanium mesh 30 is defined as the second short side), and the distance between the center of the pole lug 10 and the second short side is 5 cm.
[0110] S2: preparing electrode slurry.
[0111] This step is the same as S2 in Example 1.
[0112] S3: Prepare the electrode plates.
[0113] This step is the same as S2 in Example 1.
[0114] The total thickness of the plate is equal at all locations.
[0115] Example 5
[0116] This embodiment provides a polar plate, and the preparation method thereof comprises the following steps:
[0117] S1: preparing a titanium mesh 30 with a tab 10 .
[0118] A titanium plate made of titanium-nickel alloy with a thickness of 2 mm was used to obtain a titanium mesh 30 with a special structure having a thickness gradient distribution through mechanical processing. Subsequently, a titanium mesh 30 with circular mesh holes was obtained through punching processing, and it was cut into a titanium mesh 30 with a width of 19 cm and a length of 33 cm. The upper surface 31 and the lower surface 32 of the titanium mesh 30 are rectangular, and the side surface is a right-angled trapezoid. It can be understood that the upper surface 31 of the titanium mesh 30 is a non-horizontal surface, and the lower surface 32 is a horizontal surface. The thickness of the thinnest part of the titanium mesh 30 is 1 mm, and the thickness of the thickest part is 2 mm. The cross-sectional schematic diagram of the titanium mesh 30 is shown in FIG. Figure 5 A titanium plate with a length of 5 cm and a width of 5 cm is used as the pole lug 10, and the pole lug 10 is welded to one long side of the titanium mesh 30 and close to the end of the titanium mesh 30 with a thinner thickness (the short side corresponding to the end of the titanium mesh 30 with a thinner thickness is defined as the first short side), and the distance between the center of the pole lug 10 and the first short side is 5 cm.
[0119] S2: preparing electrode slurry.
[0120] Under stirring, the binder PVDF, the lithium iron manganese phosphate powder after delithiation (the amount of lithium delithiation is 60wt%), and the conductive agent (by mass ratio, SP:CNT=5:3) are added to the solvent NMP in the mass ratio of 11:80:9, and finally the pore-forming agent lithium chloride is added, and the amount added is 35% of the active material. Among them, the lithium iron manganese phosphate powder after delithiation is obtained by immersing the lithium iron manganese phosphate powder in a hydrogen peroxide solution with a concentration of 0.25wt% for 2h.
[0121] S3: Prepare the electrode plates.
[0122] The titanium mesh 30 with the pole ear 10 obtained in S1 is fixed on the coating mold, and then the electrode slurry obtained in S2 is coated on the upper surface 31 and the lower surface 32 of the titanium mesh 30 to ensure that the surface of the electrode slurry coating 20 is flush with the surface of the coating mold. The coating thickness of the upper surface 31 is about 2 mm at the thinnest point, and the coating thickness of the lower surface 32 is about 2 mm. The coating area is 17 cm × 31 cm. After coating, it is dried to obtain the electrode plate.
[0123] The total thickness of the plate is equal at all locations.
[0124] Example 6
[0125] This embodiment provides a polar plate, and the preparation method thereof comprises the following steps:
[0126] S1: preparing a titanium mesh 30 with a tab 10 .
[0127] A titanium plate made of titanium-molybdenum alloy with a thickness of 2 mm was used to obtain a titanium mesh 30 with a special structure having a thickness gradient distribution through mechanical processing. Subsequently, a titanium mesh 30 with square mesh holes was obtained through punching processing, and it was cut into a titanium mesh 30 with a width of 19 cm and a length of 33 cm. The upper surface 31 and the lower surface 32 of the titanium mesh 30 are rectangular, and the side surface is a right-angled trapezoid. It can be understood that the upper surface 31 of the titanium mesh 30 is a horizontal surface, and the lower surface 32 is a non-horizontal surface. The thickness of the thinnest part of the titanium mesh 30 is 1 mm, and the thickness of the thickest part is 2 mm. The cross-sectional schematic diagram of the titanium mesh 30 is shown in FIG. Figure 6 A titanium plate with a length of 5 cm and a width of 5 cm is used as the pole lug 10, and the pole lug 10 is welded to one long side of the titanium mesh 30 and close to the end of the titanium mesh 30 with a thinner thickness (the short side corresponding to the end of the titanium mesh 30 with a thinner thickness is defined as the first short side), and the distance between the center of the pole lug 10 and the first short side is 5 cm.
[0128] S2: preparing electrode slurry.
[0129] Under stirring, the binder PVDF, the lithium manganate powder after delithiation (the amount of lithium delithiation is 40wt%), and the conductive agent (by mass ratio, SP:CNT=5:3) are added to the solvent NMP in the mass ratio of 5:85:10, and finally the pore-forming agent magnesium chloride is added, and the amount added is 35% of the active material. Among them, the lithium manganate powder after delithiation is obtained by soaking the lithium manganate powder in a potassium permanganate solution with a concentration of 0.5wt% for 2h.
[0130] S3: Prepare the electrode plates.
[0131] The titanium mesh 30 with the pole ear 10 obtained in S1 is fixed on the coating mold, and then the electrode slurry obtained in S2 is coated on the upper surface 31 of the titanium mesh 30 to ensure that the surface of the electrode slurry coating 20 is flush with the surface of the coating mold. The thickness of the coating at the thinnest point is about 2 mm, and the coating area is 17 cm×31 cm. After the coating is completed, it is dried to obtain the electrode plate.
[0132] The total thickness of the plate is equal at all locations.
[0133] Comparative Example 1
[0134] This comparative example provides a polar plate, and its preparation method comprises the following steps:
[0135] S1: preparing a titanium mesh 30 with a tab 10 .
[0136] The difference between this step and S1 in Example 1 is that the titanium plate with a width of 19 cm and a length of 33 cm has the same thickness (all 0.7 mm) at each position.
[0137] S2: preparing electrode slurry.
[0138] This step is the same as S2 in Example 1.
[0139] S3: Prepare the electrode plates.
[0140] This step is substantially the same as S2 in Example 1. The coating thickness of the electrode slurry coating 20 on the upper surface 31 and the lower surface 32 of the titanium mesh 30 is about 2 mm. The side cross-sectional view of the electrode plate is as shown in FIG. Figure 7 shown.
[0141] Comparative Example 2
[0142] This comparative example provides a polar plate, and its preparation method comprises the following steps:
[0143] S1: preparing a titanium mesh 30 with a tab 10 .
[0144] The difference between this step and S1 in Example 1 is that a titanium plate with a width of 19 cm and a length of 33 cm is used with the same thickness (all 2 mm) at each position.
[0145] S2: preparing electrode slurry.
[0146] This step is the same as S2 in Example 1.
[0147] S3: Prepare the electrode plates.
[0148] This step is substantially the same as S2 in Example 1. The coating thickness of the electrode slurry coating 20 on the upper surface 31 and the lower surface 32 of the titanium mesh 30 is about 2 mm.
[0149] Comparative Example 3
[0150] The difference between this comparative example and Example 1 is that the thickest thickness of the electrode slurry coating 20 disposed on one side of the titanium mesh is 1.5 mm.
[0151] Comparative Example 4
[0152] The difference between this comparative example and Example 1 is that the surface of the titanium mesh 30 on which the electrode slurry coating 20 is disposed is rectangular, and the length ratio of the long side to the short side of the rectangle is 1.2:1 (the short side is 19 cm).
[0153] Comparative Example 5
[0154] The difference between this comparative example and Example 1 is that the surface of the titanium mesh 30 on which the electrode slurry coating 20 is disposed is rectangular, and the length ratio of the long side to the short side of the rectangle is 2.5:1 (the short side is 19 cm).
[0155] Comparative Example 6
[0156] The difference between this comparative example and Example 1 is that the tab 10 is arranged at the center of the long side, that is, the distance between the tab 10 and the first short side and the second short side is equal.
[0157] Test example
[0158] The plates prepared in Examples 1 to 6 and Comparative Examples 1 to 6 were tested for physical properties and electrochemical properties. The test methods are as follows:
[0159] ①、Test the resistance of titanium mesh 30 and plate: Use the resistor 40, clamp the pole ear 10 at one end, and connect the other end to the titanium mesh 30 or the plate surface farthest from the pole ear 10 (test diagram as shown in Figure 8 ), record the resistance.
[0160] ②. Single-sided coating surface density: calculated as single-sided coating surface density = (weight of the plate after drying - weight of titanium mesh 30) / 2 / coating area.
[0161] ③. Electrochemical lithium extraction performance test: Install in the order of end plate / electrode plate / anion membrane / electrode plate / end plate, connect the two plates to the positive and negative terminals of the blue electric tester respectively, and then introduce brine (the composition of brine is shown in Table 1) into the positive and negative chambers respectively. In the voltage range of -0.35V to 0.35V, first use 11A / m 2 The current density was 25 and 30 A / m 2 The charge and discharge lithium extraction performance test was carried out at a current density of , and the test results are shown in Table 2.
[0162] Table 1 Brine composition
[0163]
[0164] Table 2 Test results
[0165]
[0166]
[0167] From the comparison between Examples 1 to 6 and Comparative Example 1 in Table 2, it can be seen that the plate proposed by the embodiment of the present invention has a lower voltage drop and better lithium extraction performance. This is because the increase in the thickness of the plate will reduce the voltage drop of the titanium mesh 30, which promotes the improvement of the uniformity of the potential distribution on the surface of the plate, which further shows that the solution proposed by the invention has certain feasibility. At the same time, by comparing Example 1 with Examples 2 to 3, it can be seen that as the thickness of the thinner part of the titanium mesh 30 decreases, the resistance of the titanium mesh 30 and the voltage drop of the plate increase, resulting in a decrease in the stability of the lithium extraction performance.
[0168] Combining the results of Example 1 and Example 4, it can be seen that the position of the pole ear 10 has a certain influence on the cycle stability. This is because the corresponding coating thickness at the thin titanium mesh 30 is thicker, and the closer the thick coating is to the pole ear 10, the higher the voltage (the closer to the design value), which means that more active substances can fully exert the lithium extraction performance. Although the thickness gradient distribution of the titanium mesh 30 can reduce part of the voltage drop generated by the titanium mesh 30 itself, it cannot completely offset the voltage drop of the titanium mesh 30 itself. Therefore, the performance of Example 1 is better.
[0169] Combining the results of Example 1 and Comparative Example 2, it can be seen that although Comparative Example 2 has lower resistance and lithium extraction performance, its surface density is lower and the amount of titanium material used is higher, which is not conducive to reducing material costs. Considering the comprehensive cost and performance, Example 1 is better.
[0170] Combining the results of Example 1 and Comparative Examples 3 to 6, it can be seen that if the thickness of the electrode slurry coating, the size of the titanium mesh, and the location of the tabs are inappropriate, the physical properties and electrochemical performance tests of the electrode plate will deteriorate.
[0171] In summary, in the electrode plate provided by the present invention, the slurry coating thickness at the thick titanium mesh 30 is thinner, and the slurry coating thickness at the thin titanium mesh 30 is thicker, and finally an electrode plate with uniform thickness is obtained. Because the pole ear 10 is arranged at one end of the long side, the voltage drop at both ends increases with the increase of the length of the long side. By changing the thickness of the titanium mesh 30 at different positions, the voltage drop generated by the titanium mesh 30 itself can be effectively reduced, and the uniformity of the electrode potential distribution can be improved, thereby reducing the polarization of the electrode plate, which is conducive to the performance of the lithium extraction of the slurry at a distance. In addition, the electrode plate provided by the present invention can ensure a high slurry coating amount while ensuring the consistency of the voltage distribution.
[0172] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A plate, characterized in that: The electrode plate includes a titanium mesh and an electrode slurry coating disposed on at least one side of the titanium mesh; The electrode plate has a first end and a second end that are arranged opposite to each other, either of the first end and the second end is a current input end, and the other end is a current output end; along the direction from the first end to the second end, the thickness of each position of the electrode plate is equal and the titanium mesh has a thickness variation section.
2. The electrode plate according to claim 1, characterized in that: Along the direction from the first end to the second end, the thickness of the thickness-varying section gradually increases or gradually decreases.
3. The electrode plate according to claim 1, characterized in that: The thickness of the titanium mesh is 0.7 mm to 3 mm, and the thickness of the electrode slurry coating disposed on the surface of any one side of the titanium mesh is ≥ 2 mm.
4. The electrode plate according to any one of claims 1 to 3, characterized in that: The surface of the titanium mesh where the electrode slurry coating is arranged is rectangular, and the length ratio of the long side to the short side of the rectangle is 1.5:1 to 2:
1.
5. The electrode plate according to claim 4, characterized in that: The electrode plate further comprises an electrode ear, and the electrode ear is arranged on the long side of the rectangle; Preferably, the thickness of the thickness variation section gradually increases along the direction from close to the pole ear to away from the pole ear; Preferably, 0≤the distance between the tab and a short side of the rectangle≤1 / 3 of the length of the long side of the rectangle.
6. A method for preparing a polar plate according to any one of claims 1 to 5, characterized in that: The following steps are involved: The electrode slurry is coated on at least one side of the titanium mesh and dried.
7. The preparation method according to claim 6, characterized in that: The titanium mesh is made of at least one of pure titanium and titanium alloy. Preferably, the titanium alloy includes at least one of a titanium-copper alloy, a titanium-nickel alloy, a titanium-palladium alloy and a titanium-molybdenum alloy.
8. The preparation method according to claim 6, characterized in that: The raw materials for preparing the electrode slurry include a lithium-removing active material, a conductive agent, a binder and a solvent; Wherein, the mass ratio of the delithiation active material, the conductive agent and the binder is (80-85):(6-10):(5-11); Preferably, the de-lithium active material is obtained by partially reducing the active material with an oxidizing solution, and the active material includes one of lithium iron phosphate, lithium-rich manganese-based, lithium iron manganese phosphate and lithium manganate materials; Preferably, the lithium removal amount of the lithium-removing active material is 20% to 60%; Preferably, the oxidizing solution comprises one of a sodium persulfate solution, a hydrogen peroxide solution and a potassium permanganate solution; Preferably, the concentration of the oxidizing solution is 0.25 wt% to 0.5 wt%.
9. The preparation method according to claim 8, characterized in that: The preparation raw materials also include a pore-forming agent; Preferably, the pore former comprises a soluble salt; Preferably, the pore-forming agent comprises at least one of sodium chloride, lithium chloride and magnesium chloride; Preferably, the mass of the pore former is 5% to 40% of the active material.
10. Use of the electrode plate according to any one of claims 1 to 5 in electrochemical lithium extraction; Preferably, the electrode plate is used for electrochemical lithium extraction from salt lakes.